Representasi Mahasiswa dalam Memecahkan Masalah Pembuktian Geometri - Rohmatin, Dian Novita; Sunardi, Sunardi; susanto, Susanto; Suwito, Abi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
Problem-solving skills are related to other abilities, such as conceptual understanding, application of concepts, representation, and communication of ideas. When solving problems, we must understand the problem and can do this by providing an appropriate representation of the problem. Accurate representation offers a greater opportunity to achieve the desired solution. Therefore, research on students' representations in problem-solving is essential to provide an overview of how students form representations when solving geometric problems. This study uses a qualitative approach with a descriptive method. The research subjects are three students from the mathematics education program at Unipdu with high, medium, and low abilities. The results show that the low-ability subject uses pictorial representation and cannot solve the problem. The medium-ability subject uses schematic and symbolic representations but with less perfection in usage, so even though the solution found is correct, it is presented in a less structured manner. Meanwhile, the high-ability subject uses schematic and symbolic representations and finds solutions in a more structured way. Keywords: Representation, Problem-Solving, Geometry